Financial Incentives for Reducing Smoking and Promoting Other Health-Related Behavior Change in Vulnerable Populations. (March 2017) - Higgins, Stephen T.; Davis, Danielle R.; Kurti, Allison N.
Substantial reductions in U.S. cigarette smoking and associated chronic diseases over the past 50 years have benefited health. Unfortunately, those reductions have distributed unevenly throughout the population. Smoking remains prevalent and even increasing among certain vulnerable populations: economically disadvantaged groups, those with other substance-use disorders or mental illness, certain ethnic and racial minorities, and gender and sexual minorities. Moreover, other unhealthy behavior patterns (physical inactivity, unhealthy food choices, risky sexual behavior, poor adherence to medical preventive regimens) and associated chronic diseases are also overrepresented in many of these same populations. Disparities in unhealthy behavior patterns contribute to health disparities and escalating health care costs, underscoring the need for more effective behavior-change strategies. This report reviews research on the efficacy of financial incentives for reducing smoking in vulnerable populations, while also touching on applications of that behavior-change strategy for promoting other health-related behavior changes in vulnerable populations.